O plano de formação no contexto da pedagogia da alternância: articulações entre temas geradores e conteúdos do ensino médio na Casa Familiar Rural de Cruz Machado - PR - Mattos, Luciane Maria Serrer de (2014)
In recent decades the field of education has been evidenced, gaining ground in the national political agenda. It is observed that there is concern offer for young people living in the countryside a differentiated education that meets their interests and expectations. One of the ways pointed out by many scholars to make the necessary adjustments for the provision of a consistent education with the needs of individuals living in rural areas with regard to implementation of the Pedagogy of Alternation. For implementation of its proposal, the Pedagogy of Alternation has specific pedagogical tools resulting from a higher planning known as Training Plan. This Training Plan provides content that young people have access in the period of its formation and articulates the experiential knowledge and general and vocational training. It is in this context therefore that this research is part and has the following objective: to investigate how is the relationship between Themes generators and provided content for Secondary Education in Rural Family House Cruz Machado, Paraná. This research can be characterized as a field, explanatory and descriptive. Data collection was performed by means of simple observation of meetings where the monitors discuss about the themes generators and Training Plan. Were carried out also focused interviews with the instructors of Rural Family House Cruz Machado and pedagogical coordinator of ARCAFAR-South on the Pedagogy of Alternation, Themes generators and Training Plan. For data analysis, we used the Minayo (1992) explains that three important phases: data ordering, data classification and final analysis. The analysis based on the collected data showed that the monitors of Rural Family House searched produce a Plan of Training and seek to articulate Themes generators with high school content. However, the relationship is not always so explicitly. The link between Themes generators and high school content is configured, therefore, the context in which the research was conducted, as a challenge.